2014
DOI: 10.1007/s40626-014-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Photoinhibition in a C4 plant, Zea mays L.: a minireview

Abstract: Light and oxygen are both essential to life but can also cause some damage to plant photosynthesis and productivity, particularly excess light in the presence of oxygen. This phenomenon is called photoinhibition, i.e. the photooxidative damage of photosystems due to excess light associated or not with abiotic stresses. To tolerate photoinhibition, the plant needs to be able to avoid or tolerate excess light or to repair the photodamage by maintaining the de novo D1 protein synthesis that is essential for PS II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Therefore, it can be observed that Fv/Fm is strongly correlated with the physiological characteristic of genotype tolerance to water deficit. This is due to the fact that water is the major donor of electrons to photosystem II by means of the oxidation process; thus, a reduction in water content may decrease the electrochemical potential of ATP synthase and photosystem I, compromising the formation of ATP and NADPH, respectively, and negatively affecting the photosynthetic apparatus (PIMENTEL, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be observed that Fv/Fm is strongly correlated with the physiological characteristic of genotype tolerance to water deficit. This is due to the fact that water is the major donor of electrons to photosystem II by means of the oxidation process; thus, a reduction in water content may decrease the electrochemical potential of ATP synthase and photosystem I, compromising the formation of ATP and NADPH, respectively, and negatively affecting the photosynthetic apparatus (PIMENTEL, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the photoinhibition can be measured by the reduction of the potential quantum efficiency of photosystem (PS) II (Fv/Fm) (LONG et al, 1994). This index represents the energy transmitted to the PSI by the electron transport chain and is converted into chemical energy (PIMENTEL, 2014). The Fv/Fm ratio can vary within a range of 0.75 to 0.85 for normal plants in optimum conditions (KRAUSE;WEIS, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Plants have some protective mechanisms to prevent severe damages to the photosynthetic apparatus, which include repairing and replacing D 1 proteins in the Reaction Centers of Photosystem II (PSII), until dissipation of excess light energy (Baker, 2008), as in the xanthophyll cycle, which seems to be one of the most important mechanisms of PSII excess energy dissipation, in the form of heat. In addition to these, other processes, such as the pseudocyclic photophosphorylation, the ascorbate glutathione cycle and the photorespiration, contribute to reduce the photoinhibitory effect, by the consumption of the NADPH 2 produced in photosystems (Pimentel, 2014). In the xanthophyll cycle, violaxanthin is epoxidized and reduced to zeaxanthin during the day under high PPFD and stresses, consuming part of the excess electrons in the photosystem, and at night, with a lower metabolism, zeaxanthin is gradually de-epoxidized to violaxanthin, thus reducing the photoinhibitory effect (Takahashi and Badger, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the variables obtained by the emission of chlorophyll a fluorescence is already a well known technique, and is used in several work areas to discriminate between the effects of stress (Pimentel, 2014). Studies conducted to better understand the relationship between 3 these chlorophyll a fluorescence emission variables and the photosynthetic potential associated with the physiological conditions of the plant under study became frequent, due to the development and commercial availability of fast and low cost portable fluorometers, compared to other photosynthetic activity measuring equipments, which helped the use of this methodology in evaluations and in the selection of a large number of plants (Murchie and Lawson, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation